THE DOWNSTREAMING OF LIBRARY RESEARCH IN THE DEVELOPMENT ISAMIC SCIENCE - Muhamad Fajri (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This study aims to analyze and find out the detailed steps in the process and completion of library research and identify the scope of Islamic studies and opportunities for library research in the development of Islamic science. Utilization of this type of library research with an interpretation approach and using content analysis is an effort to achieve the two aims of this study. The results of this study indicate that there are six systematic steps in conducting library research, which are referred to as corner notes (1) determining the topic and specifying keywords; (2) records of search results and collection of information on topics based on keywords; (3) notes on determining the focus of the study, accompanied by problem identification, research objectives and significance; (4) inventory records of secondary and primary data based on research subjects and objects; (5) records of data presentation with the classification of themes and sub-themes of the findings of the data inventory; and (6) research report notes, which can be in the form of quotation notes. The object of study in order to downstream library research in the development of Islamic science is determined based on the discussion of the Qur'an and Sunnah as well as the works of previous scholars during the heyday of Islam. The results of each study can actually provide a stimulus for follow-up research plans.